Penggunaan Daun Binahong & Daun Petai Cina Dalam Proses Penyembuhan Luka Bakar Pada Tikus Putih - Widayati, Dhina; Milasari, Nur (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Burns are a form of tissue damage caused by contact with a heat or cold source. Indonesia is rich in herbal plants, including binahong leaves and chinese petai leaves which contain compounds for the angiogenesis process and collagen formation in the wound healing process. This study aims to determine the comparative effectiveness of binahong leaves (Anredera cordifolia) and petai cina leaves (Leucaena leucocephala) in the healing process of Grade II burns in white rats. This type of quasi-experimental research uses a post-test only design approach. The sample consisted of 18 white mice which were divided into the binahong leaf intervention group and the petai cina leaf intervention group. The sampling technique uses random sampling. The independent variable in this study was wound treatment using binahong leaves, while the dependent variable was the healing process for grade II burns. Data were analyzed using the Mann-Whitney Test with α=0.05, it was found that ρ=0.001 ≤ α(0.05) showed that there was an effect of using binahong leaves on the healing process of grade II burns with a difference of 2 days, it was faster to use binahong leaves because binahong leaves contains saponin and flavonoid compounds which can accelerate wound healing. The wound healing process using binahong leaves took an average of 11 days, while the wound healing process using the petai cina leaf group took an average of 13 days. Binahong leaves can be used as an alternative in wound care. Families can plant this plant as a family medicinal plant which can be used as herbal medicine.